NORTHWEST AFRICA (NWA) 12563 and ungrouped C2 chondrites: Alteration styles and relationships to asteroids. (15th October 2021) - Hewins, R.H.; Zanetta, P.-M.; Zanda, B.; Le Guillou, C.; Gattacceca, J.; Sognzoni, C.; Pont, S.; Piani, L.; Rigaudier, T.; Leroux, H.; Brunetto, R.; Maupin, R.; et al.
Abstract: Many asteroids in the main belt have spectra like those of Mighei-type CM chondrites, but some Near Earth Objects (NEO) resemble less well known types of C2 chondrite. Northwest Africa (NWA) 12563, a new find with affinities to C2 chondrites, could help us understand the differences between observations of CM2 chondrites and bodies that are currently being studied by the Hayabusa2 and OSIRIS-REx space missions. NWA 12563 contains 14% chondrules supported by 86% fine grained matrix consistent with CM2 chondrites, but differs from them in other respects. In both matrix and chondrules, olivine is unaltered and pyroxene shows incipient alteration. Metal in chondrules is pseudomorphed by serpentine, and mesostasis is replaced by serpentine-saponite and chlorite. Many Type I chondrules have highly irregular shapes resulting from fracturing and selective metal replacement. Type II porphyritic chondrules are clusters of phenocrysts set in matrix-like material. Type II chondrules may be kinked and partially disbarred. The matrix of NWA 12563 differs from CM2 chondrites in the absence of tochilinite-cronstedtite intergrowths. It contains hydrated and oxidized amorphous silicate (Fe 3+ /∑Fe 75%) richer in magnesium than in other chondrites (with embedded sulfides). Serpentine-saponite is also present, as well as abundant framboidal magnetite. NWA 12563 has similarities to a number of ungrouped magnetite-rich and 18 O-rich chondrites (Bells, Essebi, Niger I, WIS 91600, Tagish Lake, and MET 00432) that we call C2-ung1, as opposed to C2-ung2 chondrites (poorer in 18 O and magnetite). The oxygen isotopic composition coupled with a magnetic susceptibility of log χ = 4.67 places NWA 12563 with these ungrouped chondrites in a cluster distinct from CM2 chondrites. NWA 12563 is closest to WIS 91600 among the C2-ung1 chondrites in alteration style and light element compositions. WIS 91600, however, has suffered light thermal metamorphism, suggesting that NWA 12563 might represent its altered but unheated precursor material within the same parent body if it were zoned. The average Vis-NIR spectrum of NWA 12563 matches the asteroid taxonomic class K and resembles that of CO3 Frontier Mountain (FRO) 95002, but its spectra range from very "red" in dark matrix areas and very "blue" in magnetite-rich areas. The average MIR spectrum shows features indicating phyllosilicates, aliphatic CH compounds, hydrated silicates, and olivine. It is significantly different from those of other chondrites including FRO 95002, and closest to Bells (from which it differs in carbon isotopic composition) and WIS91600. The variety of mineralogical, chemical and isotopic properties among C2-ung1 chondrites requires several different parent bodies. However, the high abundance of magnetite common to this cluster of ungrouped chondrites, and to a lesser extent CI chondrites, indicates that they should be considered as possible material from Bennu, which has an 18 µm magnetite signal in its spectrum not seen in the CM2 chondrites (Hamilton et al., 2019).